Speech versus Writing in the Discourse of Linguistics - Robert de Beaugrande, (Miscelánea: A Journal of English and American Studies, 2006)
The relation between spoken language and written language has long remained a clouded and delicate issue. Apart from the classical rhetoric of the ancient Greeks, traditional studies generally just assumed that written language was the obvious field of inquiry. As if in defiance of tradition, “modern linguistics” declared itself to be solely devoted to spoken language, especially to build upon the foundation all successes of phonetics and phonology, but found this principle impractical to sustain. The result has been a rather narrow and incomplete picture of language, deprived of due concern for intonation and prosody. The present paper proposes and briefly demonstrates a more constructive dualism.
Keywords: spoken language; written language; prosody; corpus; authentic data